Barriers and Facilitators for Sustainability of Tele‐Homecare Programs: A Systematic Review. (26th June 2015) - Radhakrishnan, Kavita; Xie, Bo; Berkley, Amy; Kim, Miyong
Abstract : Objective: To identify the barriers and facilitators for sustainability of tele‐homecare programs implemented by home health nursing agencies for chronic disease management. Data Sources: English‐language articles on home telehealth in the CINAHL, PubMed/MEDLINE, PsychInfo, Web of Science, and Cochrane Reviews databases published from January 1996 to December 2013. Study Design: We performed a systematic literature review. Data extraction using PRISMA guidelines and quality appraisal using the Mixed Methods Appraisal Tool (MMAT) were conducted on relevant empirical studies. Thematic analysis across the studies and narrative summaries were used to synthesize the findings from the included studies. Principal Findings: Of the initial 3, 920 citations, we identified 16 articles of moderate quality meeting our inclusion criteria. Perceptions on effectiveness of tele‐homecare programs for achieving intended outcomes; tailoring of tele‐homecare programs to patient characteristics and needs; relationship and communication between patient, nurse, and other health care professional users of tele‐homecare; home health organizational process and culture; and technology quality, capability, and usability impacted the sustainability of tele‐homecare programs. Conclusions: The findings of this systematic review provide implications for sustained usage of tele‐homecare programs by home health nursing agencies and can help such programs realize their potential for chronic disease management.